(untitled) (Педагогіка вищої та середньої школи, 2022)
In the article an author considers notion group work. Accents attention on the types of groups and psychology - pedagogical terms of their unton at junior schoolbayr, determines the tasks on the lessons of Ukrainian for implementation in groups.